KUALITAS KEHIDUPAN KERJA DITINJAU DARI KEPUASAN KERJA DAN PERSEPSI TERHADAP KINERJA - Pratiwi, Kurniasari; Himam, Fathul (Jurnal Psikologi, 2014)
Abstract N o wa d a y s ,  employees are more aware wi t h  the quality of life issue than before. Consequently, quality of worklife (QWL) also becomes an important issue in the management of human resources in an organization. HigherQWL in workplace brings positive implication to the organizational performance. This study aims to investigatethe role of work satisfaction and perceived work performance towards QWL on civil servants (PNS). This studyused a survey method; it wa s conducted in the Bantul municipality, Yogyakarta. The population of civil servantsin this municipality is 600 employees. This study comprised 150 employees as study sample that was approachedusing purposive sampling me t h o d . Three instruments were used to collect data: Quality of Work Life (QWL)scale (20 items; α = 0,867); Work Satisfaction scale (22 items; α = 0,837); and Perceived Work Performancescale (20 items; α = 0,904). Multiple regressions was used to analyze the data. The results showed wo r k satisfaction and perceived work performance had significant affects towards QWL ( F = 17,852;  p < 0,001)